Mid-range transformer based wireless power transfer system for low power devices - Leong, Kah Meng (2016)
Wireless power transfer technique for biomedical devices has drawn great interest from many researchers in the biomedical domain. Biomedical devices can be powered up either by an external power cord or by batteries. However an external power cord may limit the mobility of a patient and batteries tend to have a very limited power capacity and these methods may pose a high risk of infection towards the patient. Therefore, a wireless power transfer system is proposed to solve the problem. This study attempts to develop a mid-range transformer based wireless power transmission system which is suitable to power biomedical devices. This includes the develop of a transmitter circuit, receiver circuit, a pair of transmitter and receiver coils and transformers. This study demonstrates that magnetic coupling technique is a reliable wireless charging technique biomedical devices due to its mid-range transmission and satisfactory efficiency. In order to reduce power loss, an impedance matching method which incorporates a step-up and step-down transformers in the transmitter and receiver circuit is proposed. This study also develops a wireless power charging system that does not emit harmful radiation towards the human body. The frequency for the system is within the range of 700 kHz to 900 kHz which is in accordance to the ICNIRP regulation. Three pairs of round-shaped transmitter and receiver coils pair have been designed and fabricated with the diameter size of 30cm, 40cm, and 50cm. The power supply and frequency generator are connected to the transmitter circuit and an oscilloscope is connected to the load of the receiver circuit. The performance results are recorded using a range from 4 centimeters to 110 centimeters and based on the tabulated results, the mid-range wireless power transfer system managed to supply a transfer efficiency of 60% at a distance of 35cm for the 30cm diameter coil, 62% at a distance of 43cm for the 40cm diameter coil and 46% at a distance of 50cm for the 50cm diameter coil.